Recent trends in packaging design based on Industrial Design registrations in Indonesia - Mardani, Andy; Prihastomo, Yoga (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
Indonesia is experiencing a significant transformation in its industrial sector, with packaging emerging as a crucial element of industrial growth. This study investigates recent trends in packaging based on industrial design applications in Indonesia from 2001 to 2023. The methodology involves analyzing data from specific databases of industrial design applications, focusing on the number of applications, their origin, and their classification according to the Locarno system. The analysis includes quantitative data on the frequency and distribution of design applications and qualitative insights from case studies. The results reveal a robust domestic industry with many applications from local entities such as research institutions and companies. The dominant categories include flexible packaging (bags, sachets, tubes) and rigid packaging (bottles, large containers), catering to various sectors like food, cosmetics, pharmaceuticals, and chemicals. International interest is also notable, with significant contributions from global corporations, highlighting Indonesia's strategic importance in the global packaging market. From 2001 to 2023, the number of domestic design applications related to packaging in Indonesia increased from 197 to 780, while foreign applications grew from 37 to 221. Although domestic filings remained higher overall, the foreign share peaked at 40.2% in 2020, reflecting a growing international interest in Indonesia's packaging design sector.